Promotion, prevention and treatment interventions for mental health in low- and middle-income countries through a task-shifting approach. (2020) - Purgato, Marianna; Uphoff, Eleonora; Singh, Rakesh; Thapa Pachya, Ambika; Abdulmalik, Jibril; van Ginneken, Nadja
Abstract: Recently, mental health and ill health have been reframed to be seen as a continuum from health to ill health, through the stages of being asymptomatic 'at risk', to experiencing 'mental distress', 'sub-syndromal symptoms' and finally 'mental disorders'. This new conceptualisation emphasised the importance of mental health promotion and prevention interventions, aimed at reducing the likelihood of future disorders with the general population or with people who are identified as being at risk of a disorder. This concept generated discussion on the distinction between prevention and treatment interventions, especially for those mental health conditions which lie between psychological distress and a formal psychiatric diagnosis. The present editorial aims to clarify the definition of promotion, prevention and treatment interventions delivered through a task-shifting approach according to a global mental health perspective.